Non-equilibrium magnetic response of canonical spin glass and magnetic glass. (12th October 2020) - Pal, Sudip; Kumar, Kranti; Banerjee, A; Roy, S B; Nigam, A K
Abstract: Time and history dependent magnetization has been observed in a wide variety of materials, which are collectively termed as the glassy magnetic systems. However, such systems showing similar non-equilibrium magnetic response can be microscopically very different and they can be distinguished by carefully looking into the details of the observed metastable magnetic behavior. Canonical spin glass (SG) is the most well studied member of this class and has been extensively investigated both experimentally and theoretically over the last five decades. In canonical SGs, the low temperature magnetic state obtained by cooling across the SG transition temperature in presence of an applied magnetic field is known as the field cooled (FC) state. This FC state in canonical SG is widely believed as an equilibrium state arising out of a thermodynamic second order phase transition. Here, we show that the FC state in canonical SG is not really an equilibrium state of the system. We report careful dc magnetization and ac susceptibility measurements on two canonical SG systems, AuMn (1.8%) and AgMn (1.1%). The dc magnetization in the FC state shows clear temperature dependence. In addition, the magnetization shows a distinct thermal hysteresis in the temperature regime below the SG transition temperature. On the other hand, the temperature dependence of ac susceptibility has clear frequency dispersion below SG transition in the FC state prepared by cooling the sample in the presence of a dc-bias field. We further distinguish the metastable response of the FC state of canonical SG from the metastable response of the FC state in an entirely different class of glassy magnetic system namely magnetic glass, where the non-equilibrium behavior is associated with the kinetic-arrest of a first order magnetic phase transition.